Well-posedness and behaviors of solutions to an integrable evolution equation - Sen Ming (Boundary Value Problems, 2020)
Abstract This work is devoted to investigating the local well-posedness for an integrable evolution equation and behaviors of its solutions, which possess blow-up criteria and persistence property. The existence and uniqueness of analytic solutions with analytic initial values are established. The solutions are analytic for both variables, globally in space and locally in time. The effects of coefficients λ and β on the solutions are given.